PEMANFAATAN LIMBAH KOLAM IKAN SEBAGAI SUMBER HARA N BAGI PERTUMBUHAN DAN HASIL JAGUNG MANIS (Jea mays saccharata) DI LAHAN GAMBUT (Utilization of Fish Pond Waste as N Source for Growth and Production Of Sweet Corn (Jea mays saccarata) Planted in Peatlands) - H,., Suparto (AGRIPEAT, 2016)
ABSTRACTThis study aims to assess the use fish pond wastes, such as pondâs water as source of N (nitrogen) forthe growth and production of sweet corn that is grown on peatland. To test this experiment, statisticallyit was employ complete randomized design (CRD) with only one factor variable, fish pond water wasdivided into five different levels time to pour water : AL0 = control, AL1 = every 2 day, AL2 = every 4day, AL3 = every 6 day dan AL4 = every 8 day and wich each three replication. Result showed thatof fish pondâs water evry 4 day can increasing growth and production of sweet corn wich was plantedon peatland farming area. The use of pondâs water as a source of N to sweet corn plantation of thepeatland farming.Keywords: N resouce, fish pondâs water, sweet corn, peatlands.